Stabilization of halide perovskites with silicon compounds for optoelectronic, catalytic, and bioimaging applications - Atanu Jana; Sangeun Cho; Abhishek Meena; Abu Talha Aqueel Ahmed; Vijaya Gopalan Sree; Youngsin Park; Hyungsang Kim; Hyunsik Im; Robert A. Taylor (InfoMat, 2024)
Abstract Silicon belongs to group 14 elements along with carbon, germanium, tin, and lead in the periodic table. Similar to carbon, silicon is capable of forming a wide range of stable compounds, including silicon hydrides, organosilicons, silicic acids, silicon oxides, and silicone polymers. These materials have been used extensively in optoelectronic devices, sensing, catalysis, and biomedical applications. In recent years, silicon compounds have also been shown to be suitable for stabilizing delicate halide perovskite structures. These composite materials are now receiving a lot of interest for their potential use in various real‐world applications. Despite exhibiting outstanding performance in various optoelectronic devices, halide perovskites are susceptible to breakdown in the presence of moisture, oxygen, heat, and UV light. Silicon compounds are thought to be excellent materials for improving both halide perovskite stability and the performance of perovskite‐based optoelectronic devices. In this work, a wide range of silicon compounds that have been used in halide perovskite research and their applications in various fields are discussed. The interfacial stability, structure–property correlations, and various application aspects of perovskite and silicon compounds are also analyzed at the molecular level. This study also explores the developments, difficulties, and potential future directions associated with the synthesis and application of perovskite‐silicon compounds.